A long-lasting, plasmin-activatable thrombin inhibitor aids clot lysis in vitro and does not promote bleeding in vivo - Sheffield, William P.; Eltringham-Smith, Louise J.; Gataiance, Sharon; Bhakta, Varsha (Thrombosis and Haemostasis, 2009)
The leech protein hirudin is a potent inhibitor of thrombin, but clinical use of recombinant hirudin is restricted by haemorrhagic risks, and complicated by hirudin’s rapid clearance from the circulation. We previously employed albumin fusion to slow hirudin variant 3 (HV3) clearance. In this study, we hypothesized that reconfiguration of the chimera, appending human serum albumin (HSA) to the N-terminus of HV3, with an intervening plasmin cleavage site, would create a slowly cleared, plasmin-activatable HV3. Potential plasmin cleavage sites were screened by expression in Escherichia coli, interposed between glutathione sulfotransferase and HV3 domains. The most reactive sequence (GSGIYR-ITY) was recreated in C-terminally His-tagged albumin fusion protein HSACHV3, expressed in Pichia pastoris yeast and purified by nickel-chelate affinity chromatography. HSACHV3 showed no thrombin inhibitory activity in the absence of plasmin, but liberated active HV3 in a time- and concentration-dependent manner in its presence. In a discontinuous clot assay involving clot-bound thrombin, HSACHV3 assisted clot lysis by limiting clot extension in a tPA- and concentration-dependent manner. Similar results were obtained in plasma at higher concentrations of HSACHV3. The chimeric protein exhibited much slower clearance in mice than unfused HV3, and indistinguishable pharmacokinetics from unfused recombinant HSA. In a mouse tail transection bleeding model, doses of HSACHV3 identical to those of HV3 that elicited a four-fold increase in the volume of shed blood were without effect. Our results suggest that HSACHV3 is a fully latent, plasmin activatable, long-lasting hirudin, of potential benefit in thrombotic disorders resistant to natural or pharmacological clot lysis.
Keywords: Hirudin; plasmin; thrombin; thrombosis; fibrinolysis